2021
DOI: 10.1016/j.toxrep.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pb, Cd, As and Hg concentration in edible parts of broiler in major metropolitan cities of Tamil Nadu, India

Abstract: Graphical abstract Possible contaminant route of heavy metals in human through chicken consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The maximum Pb concentration of 4.943 mg/kg was found in brain samples collected from the Madhya Badda Kacha Bazar area, and the lowest value was obtained from liver samples collected from the Mohammadpur area of DNCC. The concentration of lead in chicken muscle samples was higher compared to the studies done by [17,[35][36][37][38] and lower compared to that of [15,[39][40][41]. Other investigators recorded the same results (0.49 mg kg-1) from liver samples [12].…”
Section: Lead (Pb)supporting
confidence: 46%
“…The maximum Pb concentration of 4.943 mg/kg was found in brain samples collected from the Madhya Badda Kacha Bazar area, and the lowest value was obtained from liver samples collected from the Mohammadpur area of DNCC. The concentration of lead in chicken muscle samples was higher compared to the studies done by [17,[35][36][37][38] and lower compared to that of [15,[39][40][41]. Other investigators recorded the same results (0.49 mg kg-1) from liver samples [12].…”
Section: Lead (Pb)supporting
confidence: 46%
“…The food chain and poultry origin food products are most likely to be contaminated by the effluent discharges caused by rapid urbanization, fast industrialization, the use of inorganic fertilizers in crop fields, unplanned lead acid rechargeable batteries recycling, emissions of transport and dumping waste from municipal and industrial areas, contamination of water bodies, etc. [ 29 ], which can be detrimental to both the environment and public health. Industrial wastes discharged from textile and tannery factories contain hazardous heavy metals above the normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these contaminants bioaccumulate in the human and animal body, leading to serious consequences [ 30 , 31 ]. Heavy metals such as arsenic, chromium and lead in broiler meat might exhibit toxicity and a carcinogenic effect even at low concentration following a regular consumption of contaminated poultry products [ 29 ]. These heavy metals are also recognized as human carcinogenic agents by the International Agency for Research on Cancer and the United States Environmental Protection Agency [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study that involved the assessment of heavy and toxic metal concentrations of lead, cadmium, arsenic and mercury in broiler chicken conducted in four major cities of Tamil Nadu, revealed that lead concentrations in breast (MRL 0.1mg/kg) and liver (MRL 0.5mg/kg) samples exceeded the maximum residue level in all cities [13]. Similarly, arsenic was found to be in excess of excess of MRL of 0.1mg/kg in the chicken breast samples in all cities.…”
Section: Heavy Metals In Food Items and Food Packaging Productsmentioning
confidence: 99%